Mechanical, but not infective, pacemaker erosion may be successfully managed by re-implantation of pacemakers. Issue 2 (February 1994) - Griffith, M. J.; Mounsey, J. P.; Bexton, R. S.; Holden, M. P.
Abstract : OBJECTIVE–When a pacemaker box causes erosion it is usually removed and a new pacemaker implanted at a contralateral site. In this study when there was no evidence of systemic infection an attempt was made to clean and reimplant the same pacemaker in the same site. RESULTS–Over 10 years 62 patients had pacemaker reimplantation. In 18 patients the procedure was repeated a second time. Reimplantation was successful after at least six months follow up in 38 patients (61%): in nine two attempts had been made. Mean hospital stay for all patients was 21.3 days; for patients in whom the procedure was successful it was 12.5 days and for those in whom it was unsuccessful it was 35.4 days. 31 (82%) of the 38 patients in whom reimplantation was successful had no bacterial growth from wound swabs from 17/24 (71%) patients in whom reimplantation was unsuccessful (p < 0.001). Bacteria were grown from swabs from 7/8 patients with a protruding wire compared with 9/23 patients with a protruding pacemaker (p = 0.05). Thin patients and those who were older were more likely to have successful reimplantation: neither association reached statistical significance. A clinical impression of infection was not helpful. If re-implantation had been attempted only in the patients with negative wound swabs or intact skin the success rate would have been 74% at a cost of 5010 pounds per patient compared with a cost of 6509 pounds per patient for explantation and a reimplantation of a new contralateral pacemaker. CONCLUSION–These data support the hypothesis that pacemaker erosion is caused by primary infection or by a non-infective process (probably mechanical pressure). Pacemaker erosion that is not caused by infection can be successfully managed by ipsilateral reimplantation and this approach saves money.